A Simple Analyte Volatilization in Polytetrafluoroethylene (PTFE) Vessel for Spectrophotometric Determination of Boron - Risna E. Y. Adu; Roto Roto; Agus Kuncaka (Universitas Tadulako, 2021)
A simple analyte separation through an in-situ volatilization system in a polytetrafluoroethylene (PTFE) container was carried out for boric acid analysis in a food product by spectrophotometry. Separation was conducted in two teflon containers divided into the reagents compartment (outer vessel) and sample compartment (inner vessel). System optimization was done by varying the curcumin content and ethanol: water ratio. The optimum condition of the volatilization system was achieved at a curcumin concentration of 0.1% and ethanol: water ratio of 3:1. LOD and LOQ measurements, respectively, gave a value of 0.0413 mg/L and 0.1088 mg/L. The established method was used to determine boric acid content in sausage products by UV-Vis Spectrophotometry at 555 nm. The boric acid concentration in food samples was found to be 0.913-3.518 mg/kg. The separating method through in-situ volatilization systems in a polytetrafluoroethylene (PTFE) container can be used for boric acid analysis in food samples.